Control of cell differentiation by mechanical stress - Jong-Hoon Park; Takashi Ushida; Takayuki Akimoto (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Cells sense mechanical force and their physical environment to change their fate and behavior through mechanotransduction. The mechanotransduction is, by translating mechanical forces and deformations into biochemical intracellular signaling, changing gene expressions and adjusting cellular and extracellular structure. Given that mechanosensitive signaling modulates cellular functions as diverse as proliferation and differentiation, such signaling is crucial for normal tissue development and homeostasis. Here we review current evidence for the mechanical regulation of cell differentiation, specifically in musculoskeletal tissues, such as skeletal muscle, fat, bone, and cartilage.